Gender-specific effects of transthyretin on neural stem cell fate in the subventricular zone of the adult mouse - Vancamp, Pieter (Sci Rep, 2019)
Choroid plexus epithelial cells produce and secrete transthyretin (TTR). TTR binds and distributes thyroid hormone (TH) to brain cells via the cerebrospinal fluid. The adult murine subventricular zone (SVZ) is in close proximity to the choroid plexus. In the SVZ, TH determines neural stem cell (NSC) fate towards a neuronal or a glial cell. We investigated whether the loss of TTR also disrupted NSC fate choice. Our results show a decreased neurogenic versus oligodendrogenic balance in the lateroventral SVZ of Ttr knockout mice. This balance was also decreased in the dorsal SVZ, but only in Ttr knockout male mice, concomitant with an increased oligodendrocyte precursor density in the corpus callosum. Quantitative RTqPCR analysis following FACS-dissected SVZs, or marked-coupled microbeads sorting of in vitro neurospheres, showed elevated Ttr mRNA levels in neuronal cells, as compared to uncommitted precursor and glial cells. However, TTR protein was undetectable in vivo using immunostaining, and this despite the presence of Ttr mRNA-expressing SVZ cells. Altogether, our data demonstrate that TTR is an important factor in SVZ neuro- and oligodendrogenesis. They also reveal important gender-specific differences and spatial heterogeneity, providing new avenues for stimulating endogenous repair in neurodegenerative diseases.